PROFESSIONAL EXAMINATIONS. - Chamberlain, Henry T. (The Accounting Review, 1937)
This article presents problems and their solutions prepared by the Board of Examiners of the American Institute of Accountants, which were used in the C.P.A. examinations of thirty- eight States and three Territories on November 18-19, 1937. These problems constitute the first half of the examination in accounting theory and practice and are reproduced by permission. In the preparation of the solutions which follow the problems, the total time allotted has been kept in mind, in the hope that those who find this material of interest will gain some idea of the form and content of papers that may reasonably be expected under examination-room conditions. It also says that other selections from the Institute examinations and from the examinations held elsewhere will be presented in future issues of the journal "Review."